dy Find implicitly. dx dy dx 11 x²e-x + 3y² - xy = 0

Calculus: Early Transcendentals
8th Edition
ISBN:9781285741550
Author:James Stewart
Publisher:James Stewart
Chapter1: Functions And Models
Section: Chapter Questions
Problem 1RCC: (a) What is a function? What are its domain and range? (b) What is the graph of a function? (c) How...
icon
Related questions
Question
**Problem:**

Find \(\frac{dy}{dx}\) implicitly for the equation:

\[ x^2 e^{-x} + 3y^2 - xy = 0 \]

**Solution:**

Differentiate both sides of the equation with respect to \(x\). Use the product rule and chain rule where necessary.

1. Differentiate \(x^2 e^{-x}\):
   - Apply the product rule: \((u \cdot v)' = u'v + uv'\)
   - Let \(u = x^2\) and \(v = e^{-x}\)
   - \(u' = 2x\) and \(v' = -e^{-x}\)

   \[
   \frac{d}{dx}(x^2 e^{-x}) = 2x e^{-x} + x^2(-e^{-x}) = 2x e^{-x} - x^2 e^{-x}
   \]

2. Differentiate \(3y^2\):
   - Use the chain rule: \(\frac{d}{dx}(3y^2) = 6y \frac{dy}{dx}\)

3. Differentiate \(-xy\):
   - Use the product rule: \(u = x\), \(v = y\)
   - \(u' = 1\), \(v' = \frac{dy}{dx}\)

   \[
   \frac{d}{dx}(-xy) = -\left(x \frac{dy}{dx} + y \right) = -x \frac{dy}{dx} - y
   \]

Now substitute these derivatives into the equation:

\[
2x e^{-x} - x^2 e^{-x} + 6y \frac{dy}{dx} - x \frac{dy}{dx} - y = 0
\]

Combine terms with \(\frac{dy}{dx}\):

\[
(6y - x) \frac{dy}{dx} = y - 2x e^{-x} + x^2 e^{-x}
\]

Solve for \(\frac{dy}{dx}\):

\[
\frac{dy}{dx} = \frac{y - 2x e^{-x} + x^2 e^{-x}}{6y - x}
\]

**Answer:**

\[
\frac{dy}{dx
Transcribed Image Text:**Problem:** Find \(\frac{dy}{dx}\) implicitly for the equation: \[ x^2 e^{-x} + 3y^2 - xy = 0 \] **Solution:** Differentiate both sides of the equation with respect to \(x\). Use the product rule and chain rule where necessary. 1. Differentiate \(x^2 e^{-x}\): - Apply the product rule: \((u \cdot v)' = u'v + uv'\) - Let \(u = x^2\) and \(v = e^{-x}\) - \(u' = 2x\) and \(v' = -e^{-x}\) \[ \frac{d}{dx}(x^2 e^{-x}) = 2x e^{-x} + x^2(-e^{-x}) = 2x e^{-x} - x^2 e^{-x} \] 2. Differentiate \(3y^2\): - Use the chain rule: \(\frac{d}{dx}(3y^2) = 6y \frac{dy}{dx}\) 3. Differentiate \(-xy\): - Use the product rule: \(u = x\), \(v = y\) - \(u' = 1\), \(v' = \frac{dy}{dx}\) \[ \frac{d}{dx}(-xy) = -\left(x \frac{dy}{dx} + y \right) = -x \frac{dy}{dx} - y \] Now substitute these derivatives into the equation: \[ 2x e^{-x} - x^2 e^{-x} + 6y \frac{dy}{dx} - x \frac{dy}{dx} - y = 0 \] Combine terms with \(\frac{dy}{dx}\): \[ (6y - x) \frac{dy}{dx} = y - 2x e^{-x} + x^2 e^{-x} \] Solve for \(\frac{dy}{dx}\): \[ \frac{dy}{dx} = \frac{y - 2x e^{-x} + x^2 e^{-x}}{6y - x} \] **Answer:** \[ \frac{dy}{dx
Expert Solution
steps

Step by step

Solved in 2 steps with 2 images

Blurred answer
Recommended textbooks for you
Calculus: Early Transcendentals
Calculus: Early Transcendentals
Calculus
ISBN:
9781285741550
Author:
James Stewart
Publisher:
Cengage Learning
Thomas' Calculus (14th Edition)
Thomas' Calculus (14th Edition)
Calculus
ISBN:
9780134438986
Author:
Joel R. Hass, Christopher E. Heil, Maurice D. Weir
Publisher:
PEARSON
Calculus: Early Transcendentals (3rd Edition)
Calculus: Early Transcendentals (3rd Edition)
Calculus
ISBN:
9780134763644
Author:
William L. Briggs, Lyle Cochran, Bernard Gillett, Eric Schulz
Publisher:
PEARSON
Calculus: Early Transcendentals
Calculus: Early Transcendentals
Calculus
ISBN:
9781319050740
Author:
Jon Rogawski, Colin Adams, Robert Franzosa
Publisher:
W. H. Freeman
Precalculus
Precalculus
Calculus
ISBN:
9780135189405
Author:
Michael Sullivan
Publisher:
PEARSON
Calculus: Early Transcendental Functions
Calculus: Early Transcendental Functions
Calculus
ISBN:
9781337552516
Author:
Ron Larson, Bruce H. Edwards
Publisher:
Cengage Learning